Green Synthesis of NiO/TI-PCH Via Hydrotermal Method for Enhanced Catalytic Efficiency: Green Synthesis NiO/Ti-PCH melalui Metode Hidrotermal untuk Meningkatkan Efisiensi Katalitik - Yahya, Amri; Nurhayati, Lany; Utami, Setty (Sains Natural: Journal of Biology and Chemistry, 2025)
Heterogeneous catalysis is a vital field in chemical engineering, offering improved efficiency and selectivity in various catalytic processes. This study focuses on the dispersion of nickel into titanium-pillared montmorillonite (NiO/Ti-PCH) to enhance its catalytic properties. The primary objective is to synthesize and characterize the catalyst to evaluate its potential in catalytic applications, particularly in reactions requiring high surface area and stability. The synthesis of NiO/Ti-PCH was achieved through the intercalation of titanium and nickel into montmorillonite, followed by a series of characterizations using Fourier Transform Infrared Spectroscopy (FTIR), Gas Sorption Analyzer (GSA), and Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX). FTIR analysis was utilized to confirm the successful formation of Ti-O-Ni bonds, indicating the effective dispersion of nickel and titanium on the catalyst surface. GSA provided insights into the surface area and porosity of the synthesized material, while SEM-EDX offered information on the morphology and elemental composition. The results indicated a significant increase in the surface area of NiO/Ti-PCH due to the formation of titanium and nickel pillars, enhancing the accessibility of active sites for reactions. The FTIR spectra confirmed the presence of Ti-O-Ni bonds, which play a crucial role in improving catalytic activity. Additionally, the catalyst exhibited excellent thermal stability, making it suitable for high-temperature applications. In conclusion, the synthesized NiO/Ti-PCH demonstrates enhanced catalytic activity and thermal stability, positioning it as a promising candidate for various industrial applications. The findings underscore the importance of utilizing pillared clays in the development of efficient heterogeneous catalysts for sustainable chemical processes.